Energy–efficient data reporting with sink mobility support in object tracking sensor networks. (27th August 2012) - Hwang, Shiow–Fen; Lu, Kun–Hsien; Yang, Liang–Ren; Dow, Chyi–Ren; Chen, Ching–Wen
This study proposes an energy–efficient data reporting scheme that supports sink mobility in Object Tracking Sensor Networks (OTSN). To achieve energy efficiency, the proposed scheme presents an active node selection and scheduling method to save and balance the energy consumption among nodes based on a virtual grid structure. In addition, the proposed scheme develops an elegant weight function associated with active nodes, allowing active nodes to forward data to the mobile sink efficiently. This study also proposes an object tracking method. Simulation results show that the proposed scheme outperforms TNT and SNEM in terms of the energy consumption and average path length.